Forage quality and physiological performance of mowed alfalfa (Medicago sativa L.) subjected to combined light quality and drought - He, Chunxia; Zhao, Yan; Wang, Yao; Cai, Jinfeng; Gao, Jun; Zhang, Jinsong (Frontiers in Plant Science, 2022)
Alfalfa (Medicago sativa) can dwell in water-deficit habitats, where it is difficult to predict dry mass production and forage quality due to understory transmittance. Mowing is a recommended practice for alfalfa populations under drought, but its effect on forested land receives less attention. In a controlled indoor experiment, we found that drought better reduces shoot dry mass weight and crude fiber content (CFi) in blue light (33.7% red, 48.5% green, and 17.8% blue lights) than red light (71.7% red, 13.7% green, and 14.6% blue lights). Mowing decreases carbon (C) isotope signature (δ13C), CFi, and total C content in shoots, but increases their accumulations in dry mass, non-structural carbohydrates, and crude fat content (CFa). The results also demonstrated that mown alfalfa has higher starch content when exposed to green light (26.2% red, 56.4% green, and 17.4% blue lights) compared to the other two spectra. Multiple factorial regression indicated that higher soluble sugar content accounted for the increase of CFa and dry mass weight for CFi. Overall, mowing in blue-light enriched understory stands is recommended and produces high forage quality alfalfa, which can be used as a lowered crude fiber component.